Aerodynamic studies on hovering probe / Lee Chin Chun, M. Govardhan and Mohemmed Kamel Wan Ibrahim - Lee, Chin Chun; Govardhan, M.; Wan Ibrahim, Mohemmed Kamel (2006)
The present investigations aim at simulation and analysis of a hovering probe's performance. A modern design method is presented and the simulation of hovering probe is done by Computational Fluid Dynamics. The hovering probe under study consists of four raters. The central is provided for generating the necessary lift· Two side rotors provide the necessary maneuverability. The fourth rotor is designed to provide the necessary thrust. The entire probe along with the rotors is modeled using Solidworks 2004. The probe is designed for a speed of 10 m/s 10 meters height. The pressure and velocity distribution over the hovering probe is studied at various planes and analysed.